ChemInform Abstract: Copper‐Catalyzed Aerobic Radical C—C Bond Cleavage of N—H Ketimines. Issue 4 (January 2016) - Tnay, Ya Lin; Ang, Gim Yean; Chiba, Shunsuke
Abstract: The title process is applied for the synthesis of oxaspirocyclohexadienones as well as in the electrophilic cyanation of Grignard reagents.